'An online survey is less personal whereas I actually sat with the lecturer and it felt like you actually cared about what I am saying': a pedagogy-oriented action research to improve student engagement in Criminology. Issue 3 (27th May 2022) - Ike, Tarela Juliet
ABSTRACT: Student engagement plays a central role in teaching and learning, given its impact on students' retention and ability to actively participate in the learning process. This study evaluates the impact of an Interactive Action-Oriented Learning (IAOL) and teaching style on improving students' engagement in the Explaining Punishment module in a UK university by adopting McNiff's model of action research. Furthermore, it aims to fill a gap in the existing literature regarding the paucity of research on improving student engagement within the Criminology and Criminal Justice discipline. Two focus group discussions, each comprising eight students, were conducted. Additional data were collated from module evaluation, end terms results, and peer-feedback. Based on the end-term results, it was found that the inclusion of the IAOL contents and teaching style improved student engagement and student performance. Hence, this study suggests a model that provides practical outcomes that inform best practices in teaching and learning.